L'article 107 de la Loi sur la faillite et les droits des différents créanciers - Cordeau, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Section 107 of the Bankruptcy Act of Canada establishes an order of collocation of creditors in a bankruptcy which comes in conflict with the order of collocation set out in many provincial statutes, and in particular, with that set out in the Quebec Civil Code for privileges. This has resulted in numerous court debates between creditors and trustees of the bankruptcy as between different categories of creditors who have seen their rank either lowered or elevated by the application of section 107. In the first part of this article, the author examines the categories of creditors concerned by this inversion, being mainly : the landlords, the Crown and Workmen's Compensation Boards. The second part of this article focuses on conflicts between secured creditors under provincial law and preferred creditors under the Bankruptcy Act. The author emphasises the differences that evolved between Quebec case law and the case law of other provinces particularily as to the scope of application of section 107 when there is a conflict between a secured lender and a lien claimant affected by section 107, on property of the bankrupt in which the trustee in bankruptcy has little or no interest.